Lingko, Kearifan Lokal Manggarai dan Inkulturasi Teologi Katolik - Tandak, Rikardus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2019)
The church has been present and grown up throughout the centuries in human cultures. It takes part in the life of the world and builds the society by promoting Christian values through the local cultures. In that sense, wisdoms of the local communities are of particular importance. The writer argues that the so-called Lingko, the local wisdom of Manggarai, Flores, could be elaborated as means of promoting Christian values among the local people. In this article the writer put forward the main values of Lingko, such as the belief in Mori Keraeng (the Supreme Being, God the Creator), the value of brotherhood (cooperation and mutual assistance), and the role of ancestors (ceki) to intercede for humans to Mori Keraeng.